Modul Latihan Automasi Menggunakan Pengawal Logik Bolehaturcara - Son, Kian Chee (Universiti Sains Malaysia, 2006)
Since the early 1990s, several major factories in Malaysia have started to replace human power with automation machine especially in electronics field. Ideally, such automation machine can be operated automatically, or monitored by an operator. Somehow the knowledge of the operator towards automation machine is very limited due to the complicated system design. Therefore, this project is to design an automation training module using programmable logic controller (PLC) for the use of testing and simulation. This is a combination of software and hardware based project. The hardware implemented is a power circuit with all necessary electrical components such as circuit breaker to ensure the safety of the trainee. Understanding the power consumption is the success key of choosing the suitable circuit breaker for specific applications. The software incorporated in the control system are MATLAB 7.0 and CX-Programmer. MATLAB is being used because it can communicate through serial port using graphical user interface. Serial port in the PC is utilized as the control port since it has a direct connectivity for communications between PC and PLC. The main output of the system is an AC motor of a conveyor. The control system is basically controlling the start and stop time of the conveyor motor. The user can set the time and duration for the motor to turn on. This shows that the number of human operators hence the cost of operation for a factory can be reduced. It is hoped that in the future, this project will be upgraded and further developed to support extra functions for more complicated simulation. Finally, this project is to help the student especially mechatronics students to understand and to apply their understanding of automation.